The Oxford handbook of comparative administrative law - Cane, Peter, 1950-; Hofmann, Herwig; Ip, Eric Chi Yeung; Lindseth, Peter L. (Oxford, United Kingdom : Oxford University Press, 2021)
The comparative study of administrative law has a long history dating back more than 200 years. It has enjoyed a renaissance in the past 15 years or so and now sits alongside fields such as comparative constitutional law and global administrative law as a well-established area of scholarly research. This book is the first to provide a broad and systematic view of the subject both in terms of the topics covered and the legal traditions surveyed. In its various parts it surveys the historical beginnings of comparative administrative law scholarship, discusses important methodological issues, examines the relationship between administrative law and regime type, analyses basic concepts such as 'administrative power' and 'accountability', and deals with the creation, functions, and control of administrative power, and values of administration. The final part looks to the future of this young sub-discipline.0In this volume, distinguished experts and leaders in the field discuss a wide range of issues in administrative law from a comparative perspective. Administrative law is concerned with the conferral, nature, exercise, and legal control of administrative (or 'executive') governmental power. It has close links with other areas of 'public law', notably constitutional law and international law. It is of great interest and importance not only to lawyers but also to students of politics, government, and public policy. Studying public law comparatively helps to identify both similarities and differences between the way government power and its control is managed in different countries and legal traditions.
Includes bibliographical references and index.
Keywords: Comparative law; Administrative law